The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11033-011-1026-5
|View full text |Cite
|
Sign up to set email alerts
|

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia

Abstract: Expression profiling of microRNAs (miRNAs) in most diseases might be popular and provide the possibility for diagnostic implication, but few studies have accurately quantified the expression level of dysregulated miRNAs in acute myeloid leukemia (AML). In this study, we analyzed the peripheral blood mononuclear cells (PBMCs) from 10 AML patients (subtypes M1 to M5) and six normal controls by miRNA microarray and identified several differentially expressed miRNAs. Among them miR-29a and miR-142-3p were selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 47 publications
6
71
0
Order By: Relevance
“…This finding is universal among the five AML subtypes according to French-American-British classification, i.e. M1, M2, M3, M4 and M5, and may function jointly in granulopoiesis and monopoiesis 97 . Microarray platform used to perform genome wide miRNome analysis of AML samples and normal progenitor CD34 + cells identified molecular signatures associated with several cytogenetic groups.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…This finding is universal among the five AML subtypes according to French-American-British classification, i.e. M1, M2, M3, M4 and M5, and may function jointly in granulopoiesis and monopoiesis 97 . Microarray platform used to perform genome wide miRNome analysis of AML samples and normal progenitor CD34 + cells identified molecular signatures associated with several cytogenetic groups.…”
mentioning
confidence: 63%
“…Follow-up study on the influence of miR-29 and miR-142-3p on hematopoiesis in AML demonstrated a positive effect of these miRNAs on the monocytic and granulocytic differentiation (myeloid differentiation) and validated three targets involved in AML development. They used leukemia cell lines NB4, HL60, and THP-1, in which up-regulation of miR-29a and miR-142-3p expression during all-trans-retinoic acid (ATRA)-induced granulocytic differentiation and phorbol 12-myristate 13-acetate (PMA)-induced monocytic differentiation was observed 97 . It is conceivable that miR-29a and miR-142-3p promote myeloid differentiation primarily by affecting CCNT2, CDK6 and TAB2.…”
mentioning
confidence: 99%
“…Serum miR-142-3p was identified to be associated with a high recurrence risk in patients with early-stage lung adenocarcinoma, and was a putative serum marker for risk assessment (40). The expression levels of miR-142-3p and miR-29a in peripheral blood mononuclear cells may be used as novel diagnostic markers with ~90% sensitivity and ~100% specificity for the diagnosis of acute myeloid leukemia (41). During human bronchial squamous carcinogenesis, miR-142-3p, which is typically upregulated during lung development, was first downregulated at the earliest stages of carcinogenesis, and was also subsequently upregulated during later stages, suggesting that the expression of miR-142-3p may be monitored to assess cancer development (42).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that loss of target control by miR-142 may be a novel mechanism in the pathogenesis of leukemia. Guido Kobbe, 3 Gesine Bug, 4 Oliver Ottmann, 4 Wolf-Karsten Hofmann, 5 Nicolaus Kröger, 6 Walter Fiedler, 7 Richard Schlenk, 8 Konstanze Döhner, 8 Hartmut Döhner, 8 Jürgen Krauter, 1,9 …”
Section: 5%; P=0057)mentioning
confidence: 99%